Mediasi Pengetahuan Kesehatan Mental melalui Media Sosial - Prasetyo, Andhika; Yusuf, Agnes; Fajrinaldi, Fajrinaldi; Rahmadianti, Yundira Putri (HK-Publishing, 2025)
AbstractThis study aims to explore the relationship between social media use and mental health knowledge among undergraduate and postgraduate students of the Communication Science program at the University of Indonesia, class of 2024. Social media has become the primary platform for Generation Z, including students, to access information related to mental health issues. This study employs a quantitative approach using probability sampling techniques, involving 41 respondents (18.6% male and 76.7% female) who are active social media users. Data were collected through an online survey and analyzed using SPSS version 18.0. The results of the study indicate that social media use significantly influences online (? = 0.001) and offline (? = 0.003) discussions related to mental health. Both online and offline discussions significantly enhance respondents' mental health knowledge (? = 0.001 for each). However, social media use does not directly affect mental health knowledge (? = 0.196) and does not mediate the relationship between mental health discussions and mental health knowledge, either online (? = 0.345) or offline (? = 0.607). This study confirms the Media System Dependency framework, which states that the relationship between media, audiences, and social systems can influence perceptions, opinions, and behaviors. Students use social media as an information system to discuss mental health issues, which subsequently extends to face-to-face discussions within their social environment. This research highlights the importance of social media as a tool to improve mental health literacy among students. These findings provide practical and theoretical contributions to education, mental health literacy, interpersonal communication, and the use of digital media in the modern era. Keywords: mediation, social media, mental health AbstrakPenelitian ini bertujuan untuk mengeksplorasi hubungan antara penggunaan media sosial dan pengetahuan kesehatan mental di kalangan mahasiswa Sarjana dan Pascasarjana Ilmu Komunikasi Universitas Indonesia angkatan 2024. Media sosial telah menjadi platform utama bagi generasi Z, termasuk mahasiswa, untuk mengakses informasi terkait isu kesehatan mental. Penelitian ini menggunakan pendekatan kuantitatif dengan teknik probability sampling, melibatkan 41 responden (18,6% laki-laki dan 76,7% perempuan) yang aktif menggunakan media sosial. Data dikumpulkan melalui survei daring dan dianalisis menggunakan SPSS versi 18.0. Hasil penelitian menunjukkan bahwa penggunaan media sosial secara signifikan memengaruhi diskusi daring (? = 0,001) dan luring (? = 0,003) terkait kesehatan mental. Diskusi daring maupun luring secara signifikan meningkatkan pengetahuan kesehatan mental responden (? = 0,001 untuk masing-masing). Namun, penggunaan media sosial tidak secara langsung memengaruhi pengetahuan kesehatan mental (? = 0,196) dan tidak memediasi hubungan diskusi kesehatan mental dengan pengetahuan kesehatan mental baik secara daring (? = 0,345) maupun luring (? = 0,607). Penelitian ini mengonfirmasi kerangka teori Media System Dependency yang menyatakan bahwa hubungan antara media, audiens, dan sistem sosial dapat memengaruhi persepsi, opini, serta perilaku audiens. Mahasiswa menggunakan media sosial sebagai sistem informasi untuk membicarakan isu kesehatan mental yang kemudian berlanjut ke diskusi tatap muka di lingkungan sosial. Penelitian ini menekankan pentingnya media sosial sebagai alat untuk meningkatkan literasi kesehatan mental di kalangan mahasiswa. Temuan ini memberikan kontribusi praktis dan teoretis bagi pendidikan, literasi kesehatan mental, komunikasi interpersonal, dan penggunaan media digital di era modern. Kata kunci: mediasi, media sosial, kesehatan mental